2003
DOI: 10.1152/ajpcell.00470.2002
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of histamine by mouse peritoneal macrophages and a macrophage cell line, RAW264.7

Abstract: We have previously demonstrated that dietary histamine is accumulated in the spleens of l-histidine decarboxylase (HDC)-deficient mice, which lack endogenous histamine synthesis. To characterize the clearance system for dietary histamine in mice, we investigated the cell type and mechanism responsible for histamine uptake in the spleens of HDC-deficient mice. Immunohistochemical analyses using an antihistamine antibody indicated that a portion of the CD14+ cells in the spleen is involved in histamine storage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
4
9
0
Order By: Relevance
“…3C). These results are reminiscent of the previous studies that showed influx of extracellular histamine through organic cation transporter(s) (OCT) with low affinity and high capacity for histamine, such as OCT-3 [13,14]. An increase in the cytosolic histamine might result in accumulation of histamine in the granules.…”
Section: Impaired Granule Maturation Of Hdc −/− Ctmc Like Cultured Masupporting
confidence: 78%
“…3C). These results are reminiscent of the previous studies that showed influx of extracellular histamine through organic cation transporter(s) (OCT) with low affinity and high capacity for histamine, such as OCT-3 [13,14]. An increase in the cytosolic histamine might result in accumulation of histamine in the granules.…”
Section: Impaired Granule Maturation Of Hdc −/− Ctmc Like Cultured Masupporting
confidence: 78%
“…This system may contribute not only to feedback inhibition of histamine synthesis but also to suppression of Th2 cytokine production by immature basophils. Histamine transport across the plasma membrane was also reported in the other studies, indicating the involvement of OCT2 and an unknown system other than the OCT / OCTN family in addition to OCT3 (46,47).…”
Section: Mast Cells and Basophilssupporting
confidence: 74%
“…However, histamine content in the tissues of HDC −/− mice was controllable through dietary supplementation of histamine. 41,42) We found that dietary histamine accumulated in the spleen of HDC −/− mice and that macrophages were responsible for this uptake. 42) …”
Section: Regulation Of Histamine Synthesismentioning
confidence: 79%